Political marketing theory and concepts - Ormrod, Robert; Henneberg, Stephan C. M.; O'Shaughnessy, Nicholas J. 1954- (SAGE advanced marketing series, 2013)
"Political Marketing: Theories and Concepts provides students with a valuable and critical understanding of how political parties use marketing to attain their aims. Unlike other textbooks, this text explicitly focuses on the theoretical underpinnings and cutting edge concepts used by political parties, allowing students to gain key insights into how they win elections and remain in power. With an engaging and thought provoking topic selection, these field-leading authors have ensured that this often complex and theoretically advanced topic is clearly accessible for a student audience and novice researchers. Key features of each chapter include: Short chapter introduction and learning summaries ; Discussion questions to share in the classroom ; Annotated suggestions for further reading ; Lists of key terms to consider."--Publisher's website.